THE INFLUENCE OF SERVICE QUALITY ON PURCHASING DECISIONS AT RICHEESE FACTORY IN LHOKSEUMAWE CITY - Putri Rahmadhini; Nursakinah Ritonga; Sufi; Nursanjaya; Lisa Iryani (RADJA PUBLIKA, 2025)
Service quality is a dynamic condition that is closely related to products, services, human resources, as well as processes and the environment that can at least meet or even exceed the expected service quality. Service quality is one measure of success in providing a guarantee of satisfaction for consumers, if consumers are satisfied with a service, they will become loyal and devoted consumers to the company that provides the service. This study aims to determine the effect of Service Quality on Purchasing decisions at Richeese Factory Lhokseumawe City. This study uses a quantitative approach which aims to determine whether Service Quality has a Positive and Significant influence on Purchasing Decisions. The population in this study were all consumers who had bought at Richeese Factory Lhokseumawe City which was not known with certainty and the determination of the sample using the